# How do you differentiate #f(x)=e^(-6x) sin(3x)# using the product rule?

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate the function ( f(x) = e^{-6x} \sin(3x) ) using the product rule:

- Identify the two functions: ( u(x) = e^{-6x} ) and ( v(x) = \sin(3x) ).
- Apply the product rule: ( f'(x) = u'(x)v(x) + u(x)v'(x) ).
- Find the derivatives of ( u(x) ) and ( v(x) ): ( u'(x) = -6e^{-6x} ) and ( v'(x) = 3\cos(3x) ).
- Substitute the derivatives into the product rule formula: ( f'(x) = (-6e^{-6x})\sin(3x) + e^{-6x}(3\cos(3x)) ).
- Simplify the expression: ( f'(x) = -6e^{-6x}\sin(3x) + 3e^{-6x}\cos(3x) ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you differentiate #f(x)=x^2 (4x^3 - 1) # using the product rule?
- How do you differentiate #f(x)= (1-3x^2)^4* (1-x+7x^2)^4 # using the product rule?
- How do you find the derivative of #g(x)=sqrt(5-3x)#?
- How do you differentiate #xe^x#?
- How do you differentiate #f(x)=sqrt(x-(3x+5)^2)# using the chain rule.?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7